Interactions between the cellular and humoral immune responses in Drosophila. - Elrod-Erickson, M.; Mishra, S.; Schneider, D. (Current Biology, 2000)
Drosophila has highly efficient defenses against infection. These include both cellular immune responses, such as the phagocytosis of invading microorganisms, and humoral immune responses, such as the secretion of antimicrobial peptides into the hemolymph [1] [2]. These defense systems are thought to interact, but the nature and extent of these interactions is not known. Here we describe a method for inhibiting phagocytosis in Drosophila blood cells (hemocytes) by injecting polystyrene beads into the body cavity. This treatment does not in itself make a fly susceptible to Escherichia coli infection. However, when performed on flies carrying the mutation immune deficiency (imd), which affects the humoral immune response [3], the treatment results in a striking decrease in resistance to infection. We therefore carried out a sensitized genetic screen to identify immunocompromised mutants by co-injecting beads and E. coli. From this screen, we identified a new gene we have named red shirt and identified the caspase Dredd as a regulator of the Drosophila immune response. The observation that mutants with defects in the humoral immune response are further immunocompromised by blocking phagocytosis, and thus inhibiting the cellular immune response, shows that the Drosophila cellular and humoral immune responses act in concert to fight infection.